Improving creativy and learning motivation in basketball through tactical approach - Hartati Hartati; Meirizal Ursa; Bayu Hardiyono; Rendi Wira Jaya (Jurnal Cakrawala Pendidikan, 2022)
Students assumed that learning basketball is less fun and students did not seem interested in following it. The purpose of this study was to determine the effect of a tactical approach in basketball learning on creativity and motivation. The method used in this study was "pre-experimental design" method in the form of "intact-group comparison". The sample in this study was the eleventh graders of State Junior High School 4 Lubuklinggau with total sample of 60 students. The instruments used in this study were creativity and motivation questionnaires using a Likert scale calculation. The result of research creativity showed that the p-value was lower than the significance level (0.0490.05). It means that there was a significant improvement in experimental group after receiving the treatment of tactical approach model in basketball learning. Therefore, it can be concluded that there is a significant effect of the tactical approach in basketball leaning on the creativity and learning motivation of the students at State Junior High School 4 Lubuklinggau.